THE VALUE OF CHARACTER EDUCATION IN HAYYA FILMS - Rahmat Hidayat; Fhiqri Markhabi (Jurnal Sabilarrasyad, 2020)
Character education is education that develops cultural values and national character so that having and implementing these values is very important in the lives of students as members of society and religious, productive, and creative citizens. The Ministry of National Education has formulated 18 character values that will be instilled in students as an effort to build the nation's character. Media communication that is effective and can be accepted by all levels of society is film. Films that provide learning to support education are Hayya films. The value of character education depicted in this film is very supportive to increase knowledge for audiences, educators, and students. For this reason, this translator only provides a description of how to analyze the value of character education in Hayya films.